Explicating the de-bureaucratization of African public sector in the 21st century globalized world - Isinkaye, Kehinde Abiodun (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2025)
The objective of the paper is to assess the processes, methods, and challenges of de-bureaucratization of the public sector in Africa This study adopted historical approach to administrative research and used secondary sources of information. The study observed that under-development of state bureaucracy arose from the legacy of authoritarian nature of colonial rule, unethical behavior of public servants, skewed recruitment process, lack of competition among others. The paper concludes that if right strategies such as adequate funding of privatized organizations, technological development, good governance, itemization, and right pursuance of developmental agenda by the state favorable industrial policy environment, the public sector dynamism will be attained.